Observation of Bloch oscillations dominated by effective anyonic particle statistics - Weixuan Zhang; Hao Yuan; Haiteng Wang; Fengxiao Di; Na Sun; Xingen Zheng; Houjun Sun; Xiangdong Zhang (Nature Communications, 2022)
Electric circuits represent a versatile platform for simulations of exotic phenomena that are difficult to realize is condensed matter systems. Here the authors simulate particle statistics-dependent Bloch oscillations with electric circuits and observe features predicted for a model of anyons on a 1D lattice.